Higher economic growth in poor countries, lower migration flows to the OECD - Bencek, David,Schneiderheinze, Claas (Kiel Institute for the World Economy, 2020)
Comparing the emigration rates of countries at different stages of economic development, an inverse u-shape emerges. Although merely based on cross-sectional evidence, the
urn:nbn:de:101:1-2021032502171127213777
Keywords: Graue Literatur; Internationale Migration; Ursache; Kausalität; Entwicklung; Wirtschaftswachstum; Entwicklungshilfe; Statistische Analyse; International migration; economic development; development assistance